L'éducation à l'éthique de l'environnement dans le cadre de l'éducation en science et en technologie : une justification - Milagros Chavez Tortolero (VertigO)
The author focuses her thoughts on the finality of scientific and technological education, while approaching science and technology from a critical stance. Her reflections lead her to defend a component of environmental ethics in this realm of education. Raising the awareness in environmental ethics must be a transversal dimension in the teaching of science and technology. In this context, "transversal" means "pervasive" and implies that the multidimensional aspect and complex knowledge of mankind must both be taken into account. We should, however, explore the meaning of "environmental ethics". In this particular case, environmental ethics refers to the process of reflecting on, and discussing, the underpinning values of the relationship between humanity and the environment. There are ethical value systems called specific environmental ethics, which must be understood as a system of ethical codes. The first and foremost educational strategy that would include the transversal dimension of environmental ethics in scientific and technological teachings, is the dialogical dynamics that are thought provoking and help clarify this issue as a whole - not only the obvious values touched upon in rational discourse, but also the underlying values expressed in other forms of discourse practised in the artistic and philosophical milieu.